Livelihood of the fishermen in Monirampur Upazila of Jessore district, Bangladesh - Md. Rezaul Islam; Md. Nazmul Hoque; Shams Muhammad Galib; Md. Anisur Rahman (Journal of Fisheries, 2013)
The study was conducted to assess the livelihood of fishermen in Monirampur Upazila of Jessore district from July to December, 2012. The mean age and fishing experience of fishermen were 35.22±9.67 and 17.9±7.12 years, respectively. Primary occupation for majority fishermen (90%) was fishing. The mean monthly income of the household (HH) was BDT 9470±4806.89. Only 2% fishermen were landless. 4% fishermen had training on fishing/fish culture. 46% fishermen involved in NGOs for loan and savings. 52% fishermen cultivated paddy during boro (summer) season whereas only 18% cultivated paddy during aman (rainy) season. Major protein sources to the HHs (monthly) were- small indigenous species (SIS) (4.60±2.64 kg), non-SIS (6.31±4.18 kg), meat (3.54±1.67 kg), eggs (18.73±22.20 pieces), and milk (11.10±15.54 liter). The major HH expenditures were- food, education, health, furniture, cloths and others. All fishermen were vulnerable to vabadaha, a situation when water logging takes place during monsoon due to lack of sufficient water drainage system.